– ; Common agricultural policy of the European Union – Development and principles of functioning - Alexej Lissitsa; Oksana Luka; Taras Gagaljuk; Sergiy Kvaésa (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
. - , . , , - , , - . – – The following Discussion Paper depicts main principles and mechanisms of agricultural policy of European Union. The study is aimed to show the wide Russian speaking research community only a short historical background and few elements of current Agricultural Policy rules and should be seen as a starting point for further analysis and discussions.
urn:nbn:de:gbv:3:2-4567
Keywords: O13; O17; P26; P32; P48; Q15; Q18; 330